# tan 2A in Terms of A

We will learn to express trigonometric function of tan 2A in terms of A or tan 2A in terms of tan A. We know if A is a given angle then 2A is known as multiple angles.

How to proof the formula of tan 2A is equals  $$\frac{2 tan A}{1 - tan^{2} A}$$?

We know that for two real numbers or angles A and B,

tan (A + B) =  $$\frac{tan A + tan B}{1 - tan A tan B }$$

Now, putting B = A on both sides of the above formula we get,

tan (A + A) =  $$\frac{tan A + tan A}{1 - tan A tan A }$$

⇒ tan 2A =  $$\frac{2 tan A}{1 - tan^{2} A}$$

Note: (i) In the above formula we should note that the angle on the R.H.S. is half of the angle on L.H.S. Therefore, tan 60° = $$\frac{2 tan 30°}{1 - tan^{2} 30°}$$.

(ii) The above formula is also known as double angle formulae for tan 2A.

Now, we will apply the formula of multiple angle of tan 2A in terms of A or tan 2A in terms of tan A to solve the below problem.

1. Express tan 4A in terms of tan A

Solution:

tan 4a

= tan (2 ∙ 2A)

= $$\frac{2 tan 2A}{1 - tan^{2} (2A)}$$, [Since we know $$\frac{2 tan A}{1 - tan^{2} A}$$]

= $$\frac{2 \cdot \frac{2 tan A}{1 - tan^{2} A}}{1 - (\frac{2 tan A}{1 - tan^{2} A})^{2}}$$

= $$\frac{4 tan A (1 - tan^{2} A)}{(1 - tan^{2} A)^{2} - 4 tan^{2} A}$$

= $$\frac{4 tan A (1 - tan^{2} A)}{1 - 6 tan^{2} A + 4 tan^{4}}$$